Transdisciplinarity: an imperative for information behaviour research - Sarah Polkinghorne; Paul Bowell; Lisa M. Given (Information Research: An International Electronic Journal)
Introduction. Information behaviour research must be methodologically and conceptually sophisticated to generate knowledge reflecting the complexities of information engagement in people’s lives. Information behaviour research can be enriched by the concept of transdisciplinarity — a collaborative approach addressing complex societal problems, with actionable research outcomes.